Schooling Beyond COVID-19: An Unevenly Distributed Future - Brown, Gavin T. L. (Frontiers in Education, 2020)
The COVID-19 pandemic crisis has had a major impact on how schooling is done. With schools closed, teaching and learning continue dependent on information and communication technologies (ICT). To the degree that this has been a success, there is the possibility that post-pandemic societies might choose to de-school, switching to online teaching and learning only. In this perspective piece, I describe two major risks if that future were to be embraced; that is, lack of equitable access and dehumanization. My argument is that these futures already exist in pockets around the globe and we can use those experiences to evaluate those options. I suggest instead that the post-pandemic period gives us an opportunity to re-imagine what schools and schooling are for and advocate for a re-schooled society in which our investment in schools builds and develops society.